Satisfying future water demands for agriculture - Fraiture, Charlotte de; Wichelns, Dennis (Elsevier, 2010)
The global demand for water in agriculture will increase over time with increasing population, rising incomes, and changes in dietary preferences. Increasing demands for water by industrial and urban users, and water for the environment will intensify competition. At the same time, water scarcity is increasing in several important agricultural areas. We explore several pathways for ensuring that sufficient food is produced in the future, while also protecting the environment and reducing poverty. We examine four sets of scenarios that vary in their focus on investments in rainfed agriculture and irrigation, and the role of international trade in adjusting for national disparities in water endowments. Rainfed agriculture holds considerable potential but requires adequate mechanisms to reduce inherent risks. Irrigation expansion is warranted in places where water infrastructure is underinvested such as Sub-Saharan Africa. In South Asia the scope for improving irrigation performance and water productivity is high. International trade can help alleviate water problems in water-scarce areas, subject to economic and political considerations. We examine also a regionally optimized scenario that combines investments in rainfed and irrigated agriculture with strategic trade decisions. Compared to 'business as usual', this scenario reduces the amount of additional water required to meet food demands by 2050 by 80%. Some of that water could be made available for the environment and other sectors. We conclude that there are sufficient land and water resources available to satisfy global food demands during the next 50 years, but only if water is managed more effectively in agriculture.